Digital Activism and the Making of a Decolonial Public Theology: Revisiting the 2020 #Endsars Protest as a Theological Provocation - Ikenna Paschal Okpaleke (Ecclesial Futures, 2026)
This article explores the 2020 #EndSARS protest in Nigeria as a theological provocation that calls for a decolonial public theology. The protest, which demanded the disbandment of the Special Anti-Robbery Squad due to systematic police brutality, exemplified the transformation of digital activism into embodied resistance. Employing an incarnational hermeneutic, in which words were made flesh through action, I argue in this article that the protest challenged both colonial rationalities embedded in state violence and the complicity of Nigerian Christianity in structures of domination. Drawing on the decolonial framework and liberation theology of Jean-Marc Ela’s, I demonstrate how the protesters compelled churches to rediscover their prophetic voice and engage in resistive performances. The analysis reveals two forms of theological provocation: the demand for churches to speak prophetically against injustice, and the call for concrete ecclesial action in solidarity with those experiencing dehumanization. By conceptualizing the protest as an incarnational and decolonial moment, this study proposes a theology from below that critiques the colonial matrix of power, affirms the grievability of all lives, and reclaims Christianity’s radical commitment to abundant life and social transformation in postcolonial Africa.